A Moderate Intake of Beer Improves Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) in a High-Fat Diet (HFD)-Induced Mouse Model - Andrea Vornoli; Aymen Souid; Barbara Lazzari; Federica Turri; Flavia Pizzi; Emilia Bramanti; Beatrice Campanella; Cheherazade Trouki; Andrea Raffaelli; Marta Wójcik; Clara Maria Della Croce; Lucia Giorgetti; et al. (Molecules)
Beer and its components show potential for reducing hepatic steatosis in rodent models through multiple mechanisms. This study aimed to evaluate beer’s anti-steatotic effects in a high-fat diet (HFD)-induced mouse model of Metabolic dysfunction-Associated Liver Disease (MASLD) and to explore the underlying mechanisms. In the HFD group, steatosis was confirmed by altered blood parameters, weight gain, elevated liver lipid content, and histological changes. These markers were normalized in the HFD+beer group, reaching levels similar to the control (CTR) group. Protein carbonylation and lipid peroxidation levels were consistent across all groups, suggesting that the model represents an early stage of MASLD without oxidative stress. Transcriptomic and CpG methylation analyses revealed clear distinctions between the CTR and HFD groups. RNA sequencing identified 162 differentially expressed genes (DEGs) between the CTR and HFD groups, primarily related to inflammation and lipid regulation. Beer consumption modified the health of the HFD mice, affecting inflammation but not lipid homeostasis (CTR vs. HFD+beer, DEGs = 43). The CpG methylation analysis indicated that beer lowered methylation, impacting genes linked to lipid accumulation and inflammation. A cecal metabolite analysis suggested that beer improved short-chain fatty acid metabolism (SCFA). In summary, a moderate beer intake may mitigate MASLD by modulating lipid metabolism and SCFA pathways, likely through polyphenol activity.